A grounded theory approach to the subjective understanding of urban soundscape in Sheffield. (February 2016) - Liu, Fangfang; Kang, Jian
Abstract: The aim of this study is to gain a greater insight into the factors that affect individuals' preferences and understanding of urban soundscapes. Based on a grounded theory approach, with 53 participants in Sheffield, five categories have been revealed for the subjective understanding of soundscape: soundscape definition, soundscape memory, soundscape sentiment, soundscape expectation, and soundscape aesthetics. More specifically, to some extent, the value people place on sounds does not lie in the sound itself or its physical properties but in the positive or negative behaviors associated with sounds. Some long-term soundscape memory was preserved because the sounds correlated to something profound in people's mind to some degree. Most people like to use two evaluation criteria, namely favorite sound and annoying sound, to reflect their soundscape sentiment, but emotion is also an important part of psychological stratification, which includes joyful, angry, sad, despair, and afraid. People hope that soundscape will change as time goes by, towards the soundscape of natural and comfortable sounds mixed with entertainment, as well as simple sounds containing peaceful and joyful information; notably, people look forward to more electronic, comfortable, and technical sounds in the future. Soundscape aesthetics in the future reflect a presupposition for future-oriented aesthetic judgment. Highlights: Past, present and future soundscapes examined using grounded theory Soundscape categories revealed: definition/memory/sentiment/expectation/aesthetics Value of sounds lies on the positive or negative behaviors associated with sounds. Emotion (joyful/angry/sad/despair/afraid) important for psychological stratification Soundscape should change to natural and comfortable sounds mixed with entertainment.